Electrocatalytic oxygen reduction to hydrogen peroxide by oxidized graphene aerogel supported cubic MnCO3 for antibacteria in neutral media. (20th April 2020) - Wang, Nan; Ma, Shaobo; Duan, Jizhou; Zhai, Xiaofan; Guan, Fang; Wang, Xiutong; Hou, Baorong
Abstract: The electrochemical synthesis of hydrogen peroxide (H2 O2 ) based on 2-electron oxygen reduction reaction (ORR), is a particularly promising alternative route for in-situ application. Herein, we prepared the oxidized graphene aerogel supported cubic manganese carbonate composites (GOx /MnCO3 ) with different GO and MnCO3 ratio through a simple co-precipitation/in-situ coating method. The GOx /MnCO3 composites, with uniformly wrapping of GO on the surface of MnCO3 cubic, display high conductivity and abundant catalytic sites for 2-electron ORR. The G0.2 M shows the best ORR catalytic performance, onset potential of 0.635 VRHE, high H2 O2 production selectivity and high stability in 3.5% NaCl electrolyte. Based on this, G0.2 M as oxygen reduction electrocatalyst, has good antibacterial effect at 0.55 VRHE on the stainless-steel. The antibacterial mechanism is mainly due to the electrocatalytic oxygen reaction of H2 O2 and the side reaction of OH and O2 - . This provides an impressive, effective and environmentally friendly electrochemical approach for antibacterial and antifouling applications.